From Genes to Gym: The Impact of Physical Exercise on Arrhythmogenic Right Ventricular Cardiomyopathy - Kucharski, Adam; Pilarski, Konrad; Makuch, Rafał; Chrościcka , Alicja; Gała, Kamil; Czajka, Andrzej; Lenard, Paweł; Michalska, Sara; Dewicka, Martyna; Wawrzyniak, Alicja Maria (Quality in Sport, 2024)
Arrhythmogenic right ventricular cardiomyopathy (ARVC) is a hereditary heart muscle disorder characterized by the progressive replacement of right ventricular myocardium with fibrofatty tissue. This condition predisposes individuals to arrhythmias and an elevated risk of sudden cardiac death (SCD). The etiology of ARVC is predominantly genetic, with mutations in genes encoding desmosomal proteins playing a crucial role. Physical exercise has a significant impact on the progression of ARVC, often exacerbating the disease’s severity and increasing the likelihood of life-threatening arrhythmic events. Diagnosing ARVC remains challenging due to its variable clinical presentation and overlapping features with other cardiomyopathies. Advanced imaging techniques, electrocardiography, and genetic testing are essential tools in the diagnostic process. Treatment strategies for ARVC include lifestyle modifications, pharmacotherapy, implantable cardioverter-defibrillators (ICDs), and in some cases, catheter ablation or heart transplantation. Preventing disease progression and SCD involves a multidisciplinary approach, emphasizing early diagnosis, risk stratification, and tailored therapeutic interventions. This review comprehensively examines the etiology of ARVC, the detrimental effects of physical exercise on the disease, the associated SCD risk, and the challenges in diagnosis, while also discussing current treatment modalities and preventive measures to mitigate disease progression. Materials and Methods Review and summary of research studies available in databases on Google Scholar and PubMed. Databases such as PubMed and Google Scholar were searched using the keywords: ‘Arrhythmogenic right ventricular cardiomyopathy, ‘ARVC in athletes’, ‘Sudden cardiac death’, ‘impact of physical exercise on ARVC’.